Inpatients Sign On: An Opportunity to Engage Hospitalized Patients and Caregivers Using Inpatient Portals. Issue 2 (February 2019) - Kelly, Michelle M.; Hoonakker, Peter L.T.; Coller, Ryan J.
Abstract : Background: Inpatient portals are online patient portals linked to electronic health records that provide hospitalized patients and caregivers secure access to real-time clinical information and tools to enhance their communication with providers and hospital experience. Objective: The main objective of this commentary was to provide a perspective that inpatient portals are innovative tools poised to engage patients and caregivers during hospitalization and, thus, enhance patient-centered care. Results: Inpatient portals are desired by patients and caregivers and may contribute to improved recognition of their inpatient care team, knowledge of their treatment plan and overall inpatient experience. A sociotechnical systems approach is recommended to mitigate potential unintended consequences of inpatient portal use and support effective portal design, implementation and evaluation. Conclusions: This article highlights the potential of using inpatient portals to engage hospitalized patients and caregivers and proposes next steps to evaluate this emerging technology.